Professionalism of new further education teachers: a metaphorical analysis - Rose, Neil (2019)
This thesis explores the possible tensions and alignments between professional standards and teachers in a general further education college in the midlands, in the further education sector (FE), and identifies the limitations for individuals given this standardised approach. The research is situated at a time when FE has been increasingly held to account for student success and increased/improved industrial productivity on the world stage. Central to this notion is the quality of the training of its teachers, which successive governments have recognised and embraced by introducing new sets of qualifications and teacher professional standards. The thesis provides a detailed view of how individuals’ socio-cultural backgrounds and life histories impact on how well they engage with the standards and what this might mean for their future professional practice. The research was conducted with four pre- and beginning teachers who attended the introductory ‘threshold licence to teach’ qualification, Preparing to Teach in the Lifelong Learning Sector (PTLLS), now the Award in Education and Training (AET). This was situated in a qualitative, interpretivist paradigm using a nested case study, mixed methods approach. Nominal Group Technique, semi structured interviews and textual analysis were employed as data gathering techniques. The analytical framework was influenced by Lakoff and Johnson’s (1981) work on contemporary theory of metaphors and was used throughout as the main methodology using a grounded, inductive approach. This thesis illuminates, through metaphor analysis, the complicated conceptual associations of pre- and beginning teachers’ socio-cultural histories and life histories and how these can fundamentally affect their future professional practice and engagement with professional standards. This raises the notion of there being multiple ways in which teachers experience their work and how trainees’ metaphors can indicate the types of professionals they are likely to be. The study thus calls for policy-makers, FE organisations, teacher trainers and ITE trainees and researchers to encourage ways that the diversity of individual trainees can be explored and utilised, by the encouragement of deeper reflexive rather than reflective practice. This will aid the improvement of FE teacher professionalism.